2023
DOI: 10.21876/rcshci.v13i4.1464
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Heart Rate Training Zones in an Exercise Training Program in Adults with Coronary Artery Disease

Patric Emerson Oliveira Gonçalves,
Tiago da Silva Nogueira,
Bruno Rezende Passos
et al.

Abstract: Objectives: To investigate the effect of exercise intensity on functional capacity in individuals with coronary artery disease, assess adherence to the heart rate training zone (HRTZ), and determine the relationship between trained intensity and functional capacity. Methods: A retrospective study was conducted on the medical records of 54 outpatients with coronary artery disease in a public hospital. The prescribed intensity started at 50%–60% of the heart rate reserve, increasing monthly to 70%–80% by the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…As we shift into a post-pandemic era, a proper approach to address health in seniors will require not only the promotion and encouragement of physical activity but also specific strategies for this vulnerable population focusing on increasing the effectiveness of overall care 6 A study in older adults with coronary disease showed a decrease in adherence to training zones measured by heart rate monitors as exercise program intensity progressed 9 . Technology offers valuable tools to help adherence and motivation to stay active by providing real-time feedback, personalized guidance, and motivation through wearable devices and apps.…”
mentioning
confidence: 99%
“…As we shift into a post-pandemic era, a proper approach to address health in seniors will require not only the promotion and encouragement of physical activity but also specific strategies for this vulnerable population focusing on increasing the effectiveness of overall care 6 A study in older adults with coronary disease showed a decrease in adherence to training zones measured by heart rate monitors as exercise program intensity progressed 9 . Technology offers valuable tools to help adherence and motivation to stay active by providing real-time feedback, personalized guidance, and motivation through wearable devices and apps.…”
mentioning
confidence: 99%